THE ANALYSIS OF MARKET SERVICE AND TOURIST ATTRACTION OBJECT PROMOTION IN RENGAT INDRAGIRI HULU DISTRICT - Warnadi Warnadi; Muhklas Adi Putra (LPPM Press STIE Indragiri Rengat, 2020)
Tourism is one of the sectors that the government relies on to earn foreign exchange from non-oil and gas income. The impact of tourism development on economic development is so large that special attention is needed. The problem in tourism objects in Rengat Subdistrict, Indragiri Hulu Regency which is the main focus in this research is the lack of marketing services to a weak service system and the promotion of attractions that are still felt to be lacking. The results of this study indicate that market opportunity analysis will determine the next step, namely the determination of strategic service concepts that are translated into market positioning and implemented in the service marketing concept. And Indragiri Hulu Regency which actually has been supported by natural conditions and potential tourism environment. Promotional mix is ​​one component of the marketing mix that plays an important role in the process of achieving the expected goals, namely to introduce, inform, persuade and influence prospective tourists to visit and keep tourists always remembering and desiring to make a return visit to Rengat City with tourism objects which exists.